PENDEKATAN PSIKOLOGI DALAM UPAYA PERSIAPAN BIMBINGAN KARIR PADA SISWA KELAS 12 SMAN 2 MAKASSAR - Iindah Dwi Cahyani Ilyas; Ahnan Murtadho; Nur Hikmah; Fitrah Ramadhani; M Ahkam Alwi (Universitas Negeri Makassar, 2024)
Students who are in high school, especially class XII, must be able to understand themselves and know which career is suitable for them. The psychoeducation program about